The Ocean and Us - An exploratory qualitative interview study on ocean-society relationships in the Maldives - Algurén-Laager,Zoë (2024)
The ocean’s importance for human survival is indisputable. However, humanity's continuous impact on the ocean negatively affects its well-being. While this interrelation is acknowledged, only a few studies research the relationship between the ocean and societies. Thus, this study aimed to explore whether specific concepts and theories are necessary when analysing ocean-society relationships. This research was conducted as an exploratory qualitative interview study and analysed the frames used by a sample of Maldivians to construct their perspectives on the ocean and their relationship with it. A social constructivist stance was adopted, and framing theory was used during the research and analysis. A typology that describes concepts and discourses used to analyse nature-society relationships was presented and guided the research. However, the study remained inductive and was open to new frames used for describing ocean-society relationships. The study analysed eight different frames that were used by the participants to construct their relationship with the ocean. Five of these frames largely conformed with concepts described in the typology section. However, three new frames were discovered that specifically related to the participants' relationship to the ocean. Therefore, this study contributed to the contemporary academic discussion by suggesting new ocean-specific frames that can be used for the analysis of ocean-society relationships. Thus, the findings of this study indicate that ocean-specific concepts, frames, discourses, and theories are necessary when researching ocean-society relationships.
Keywords: environmental sociology; ocean-society; ocean perspectives; ocean-society relationship; pro-environmental behaviour